Analisis Kepuasan Pelanggan Terhadap Pelayanan PT. POS Indonesia (Persero) Cabang Ambon Menggunakan Metode Servqual dan Lexicon Based - Febrilien Matresya Matulatuwa (Maranatha University Press, 2017)
Abstractâ€” PT. POS Indonesia (Persero) Ambon Branch is one company that is engaged in the field of services is always trying to provide the best service to the community. With the competition being so tight tight, it should the company to do is continue to keep customers want and remain faithful to use his services. The purpose of this study is to find customer satisfaction of services provided from post office Ambon branch through the questionnaire data. This research uses a servqual model and lexicon based method. Servqual model is a method of descriptive models that describe the level of customer satisfaction. Servqual model consist of five servqual dimension and GAP analysis. Lexicon based method is a simple method for analysis of the questionnaire data to the reality of service that perceived by customers. The results of this paper will be used to make post office aware of their customer satisfaction and also to identify wich part of the services needs to be improved.Â Keywordsâ€” Customer, GAP Analysis, Lexicon Based, POS Indonesia, Servqual Model.